The Position of Smart Contracts in the Light of Islamic Contract Theory - Ahmad, Azlin Alisa; Mat Zain, Mat Noor; Amanina Zakaria, Nur Diyana (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Smart contracts are simply programs stored in a blockchain that run under predetermined conditions; however, they are yet to be implemented commercially in the financial industry, including the Islamic financial industry. It has not been entirely implemented in the Islamic financial industry because it is unstable and there are debates regarding its conformity with Shariah principles. Since the development of the smart contract is still in the preliminary stages, its position in an Islamic contract is yet to be determined. Does a smart contract blockchain comply with Islamic contract theory? This qualitative study aims to analyse the smart contract’s position based on Islamic contract theory. Data were obtained using content analysis and interview methods, in which the semi-structured interview involved Islamic financial experts and industryplayers. Data were then analysed using the QDA Miner version 5.0.31 software. Findings indicate that a smart contract differs from other contracts because it records every transaction using hash cryptography and computer codes known as solidity. Besides that, transactions did not adhere to two principles of an Islamic contract, namely the existence of autonomy in the contracting parties and the ability to manipulate the contract. Hence, Shariah-based risks in a smart contract can be decreased by improving the Shariah compliance aspect in the transaction to solve autonomy issues and the manipulation of contracts. The study implies that a smart contract has the potential to become an innovation in the Islamicfinancial industry if it can adhere to the principles of an Islamic contract and it can be monitored by relevant authorities.